Kurikulum Pendidikan Agama Kristen di Indonesia - Nancy F.L. Tobing (Sekolah Tinggi Teologi Sriwijaya, 2020)
This paper explain that the curriculum of Christian education at Indonesia should stress Christianity learning and learning about Christianity. Christian education courses have an aim to distribute faith and belief with Christian attributes or characteristics that can be learned and teached, either inside or outside the classroom. The problem is the courses have a difference contexts or can be say that each student have its own context. Meanwhile, Christian education focus on achieve the first aim that is to enable every person to reach growth as fullness of Christ. For it, the process of development of Christian education curriculum needs to design and suit to Christianity value. I’ll applied literature methods to analize every design of Christian education curriculum which has been appointed by goverment. According to title of this paper, I’ll make critical observation and evaluation by analize the important thing in organizing and developing the Christian education curriculum, as one of subject that has been appointed by the government.